Mengungkap Peran Asisten Dosen dalam Mendorong Self-Regulated Learning Mahasiswa Biologi: Studi Mixed Methods Embedded - Fahrul Ghani Muhaimin; Syifa Nabila Firdausya; Ayu Chandra Mustikasari; Anas Bagaskara Witanto; Heni Refdiana; Nafi’ Windy Kharisma (Biocaster : Jurnal Kajian Biologi, 2026)
Self-regulated learning (SRL) is an essential ability that students must possess to manage their learning processes independently; however, in reality, this ability is still not optimal. One factor that has the potential to support the development of SRL is the role of teaching assistants in the learning process. This study aims to analyze the role of teaching assistants, examine their influence on the SRL of biology students, and explore the pedagogical mechanisms underlying this relationship. The study employed a mixed-methods approach with an embedded design, in which quantitative data served as the primary data and qualitative data as supporting data. The quantitative sample consisted of 207 students and 13 qualitative informants (10 students and 3 teaching assistants) selected through purposive sampling. The results showed that the role of teaching assistants was in the very high category (mean = 4.32), while students’ SRL was in the high category (mean = 4.20). The correlation value (R) of 0.630 indicates a positive relationship between the role of teaching assistants and SRL, with a contribution of 39.7% (R² = 0.397). The regression equation obtained was Y = 30.372 + 0.621X, indicating that each unit increase in the role of teaching assistants leads to an increase in students’ SRL. Pedagogically, this influence is mediated through learning facilitation, reflective feedback, and guided discussions. Therefore, teaching assistants play a strategic role in supporting students’ independent learning.